Impact of homogeneous and heterogeneous reactions in the presence of hybrid nanofluid flow on various geometries - Haq, Izharul; Naveen Kumar, R.; Gill, Rana; Madhukesh, J. K.; Khan, Umair; Raizah, Zehba; Eldin, Sayed M.; Boonsatit, Nattakan; Jirawattanapanit, Anuwat (Frontiers in Chemistry, 2022)
The current work investigates the influence of porous media, homogeneous and heterogeneous reactions, and a heat source/sink on the hybrid nanoliquid circulation on three distinct surfaces (cone, plate, and wedge). The system of equations that describe the circulation issue and operating conditions is reduced to ordinary differential equations (ODEs) by using the proper similarity transformations. The Runge–Kutta–Fehlberg 45 order and the shooting approach are used to generate the numerical results. Graphs are used to show how various dimensionless limits affect the associated profiles. The results demonstrate that, in the presence of heat source/sink and porous medium characteristics, respectively, fluid velocity and heat dispersion are high in plate geometry and lower in cone geometry. The concentration profile shows the declination in the presence of both homogeneous and heterogeneous reaction intensities. The surface drag force decreases and the rate of heat dispersion rises with the addition of a porous attribute. Furthermore, cones sprinkle the heat more quickly than wedges, which disperse heat more slowly.